2011
DOI: 10.1111/j.1532-5415.2011.03699.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effect of Function‐Focused Care in Assisted Living

Abstract: Using a function-focused approach in AL may help prevent some of the functional decline commonly noted in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 43 publications
(57 reference statements)
1
114
0
Order By: Relevance
“…Although three sets of authors (Benjamin et al, 2011;Galik et al, 2011, Resnick et al, 2011b, used a socioecological model to frame their studies, only one made explicit reference to intersecting barriers at different system levels (Benjamin et al, 2011). For instance, when inadequate staffing (an organizational-level barrier) was coupled with a lack of sufficient elevators (an environmental-level barrier), transporting residents to planned physical activities was constrained.…”
Section: Resultsmentioning
confidence: 99%
“…Although three sets of authors (Benjamin et al, 2011;Galik et al, 2011, Resnick et al, 2011b, used a socioecological model to frame their studies, only one made explicit reference to intersecting barriers at different system levels (Benjamin et al, 2011). For instance, when inadequate staffing (an organizational-level barrier) was coupled with a lack of sufficient elevators (an environmental-level barrier), transporting residents to planned physical activities was constrained.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, across all settings, we have demonstrated that we can teach caregivers (nurses, nursing assistants, and family caregivers) how to provide Function Focused Care to older adults (Burkett et al, 2013;Galik et al, 2014;Pretzer-Aboff, Galik, & Resnick, 2011;Resnick, Galik, Enders, et al, 2011;Resnick, Galik, Gruber-Baldini, et al, 2011;). The outcomes following exposure to Function Focused Care approaches for older adults vary, based on the setting and participants involved.…”
Section: Significance Of Function Focused Care Across All Settingsmentioning
confidence: 66%
“…There was no change in quality of life or life satisfaction following exposure to Function Focused Care Resnick, Galik, Gruber-Baldini, et al, 2011). The work that has been done in acute care suggests that those who are exposed to Function Focused Care either by nurses or family caregivers have better functional outcomes (Boltz et al, 2012), suggesting that there is benefit to this approach when hospitalized.…”
Section: Moodmentioning
confidence: 96%
“…When an individual demonstrates decreased ability to complete functional tasks, a routine of sedentary behavior and task avoidance develops leading to a poorer quality of life [6]. This decline in function could be explained by the limited amount of physical activity offered to the elderly or their limited participation [7]. At least 30% of individuals who enter a residential care facility show a decline in muscle strength, muscle power, cardiovascular function, and neuromuscular response times [8].…”
Section: Introductionmentioning
confidence: 99%